Autistic adults' experiences of diagnostic disclosure in the workplace: Decision-making and factors associated with outcomes. (June 2021) - Romualdez, Anna Melissa; Walker, Zachary; Remington, Anna
Autistic individuals often struggle to find and maintain employment. This may be because many workplaces are not suited to autistic individuals' needs. Among other difficulties, many autistic employees experience distracting or disruptive sensory environments, lack of flexibility in work hours, and unclear communication from colleagues. One possible way of mitigating these difficulties is for employees to disclose their diagnosis at work. While disclosure may increase understanding and acceptance from colleagues, it can also lead to discrimination and stigma in the workplace. Research has shown that disclosure outcomes are often mixed, but it is unclear what factors are associated with either positive or negative outcomes of disclosure for autistic people. This study aimed to identify these factors and explore the reasons why autistic employees choose to disclose or to keep their diagnosis private. Semi-structured interviews were conducted with 24 clinically-diagnosed autistic adults (12 male and 12 female) who were currently, or had been, employed in the UK (mean age = 45.7 years). Through thematic analysis, we identified three main themes under experiences of disclosure: 1) A preference for keeping my diagnosis private; 2) The importance of disclosure in the workplace; and 3) Disclosure has mixed outcomes. We also identified three factors associated with disclosure outcomes: understanding of autism, adaptations, and organisational culture. These results have implications for improving inclusive practices on both the individual and organisational level to ensure more positive disclosure experiences for autistic employees.